Mental health concerns and needs of international students in higher education settings: A scoping review protocol - Kira Rudakova; Shalini Lal (PLoS ONE, 2025)
Introduction The transition to higher education is a significant milestone for many individuals; however, it also brings new stressors and challenges, particularly for international students adjusting to life in a foreign country. Despite the increasing diversity of student populations globally, there remains a gap in existing reviews that capture the full scope of international student mental health concerns and needs. Existing reviews on the mental health and psychosocial adjustment of international students often concentrate on acculturation stress, thus overlooking other mental health concerns such as depression and anxiety, as well as positive mental health experiences like increased well-being. Meanwhile, other reviews tend to focus more heavily on specific regions, such as the United States and Australia, or student populations, particularly East-Asian students. While valuable, this focus may limit our understanding of the diverse mental health experiences of international students. Objective The objective of this scoping review is to map and summarize research on international students’ mental health experiences and concerns (e.g., depression) as well as factors influencing their well-being (e.g., social support and institutional resources). Methods A search strategy guided by the Joanna Briggs Institute (JBI) Manual of Evidence Synthesis has been developed according to the Population, Concern, and Context (PCC) framework and will be applied to four electronic databases (i.e., MEDLINE, Embase, PsycInfo, and CINAHL). Two reviewers will pilot the selection strategy on subsets of 10 articles until a 90% agreement rate is achieved. Once this rate is reached, a single reviewer will screen the remaining articles independently. Two reviewers will pilot data extraction on subsets of 10 included studies, after which one reviewer will proceed independently. Main findings will be presented through descriptive statistics, using tables and figures. Expected contributions This scoping review will assess existing literature on the mental health needs and experiences of international students, highlighting overlooked issues, such as challenges beyond acculturation stress and the experiences of underrepresented student populations, including those studying outside of Western countries. Ultimately, the findings may identify areas for further research and inform educational institutions and mental health professionals in developing support resources that can effectively address diverse needs of international students.